2020
DOI: 10.1002/jper.20-0176
|View full text |Cite
|
Sign up to set email alerts
|

Role of YAP1 gene in proliferation, osteogenic differentiation, and apoptosis of human periodontal ligament stem cells induced by TNF‐α

Abstract: Background Periodontitis is a chronic inflammatory disease that occurs in periodontal tissues and can cause tooth loosening and loss in severe cases. As the main effector of downstream of Hippo signaling pathway, yes‐related protein 1 (YAP1) plays an important role in cell proliferation and differentiation. However, the role of YAP1 in periodontitis has not been reported. Methods Cell activity was detected by Cell Counting Kit‐8 (CCK‐8). YAP1 was overexpressed by cell transfection, and then RT‐qPCR and western… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…And other researchers also used 20 ng/mL or 50 ng/mL TNF- α to mimic the inflammatory microenvironment, which supported results. As the same, those also reckoned that proliferation rate was evidently suppressed and inflammatory cytokines expressed most on 72 hours [ 46 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 89%
“…And other researchers also used 20 ng/mL or 50 ng/mL TNF- α to mimic the inflammatory microenvironment, which supported results. As the same, those also reckoned that proliferation rate was evidently suppressed and inflammatory cytokines expressed most on 72 hours [ 46 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 89%
“…Our analysis revealed that TNF pathway–mediated apoptosis is involved in periodontitis progression (Figure 7). TNF‐α induces apoptosis in human periodontal ligament stem cells [34] . In vitro experiments further demonstrated that Turkish galls significantly reduced the level of inflammatory cytokines IL‐6 and TNF‐α.…”
Section: Discussionmentioning
confidence: 93%
“…Consequently, transcriptional YAP targets, such as cysteine-rich angiogenic inducer 61 (CYR61) and connective tissue growth factor (CTGF), are transcriptionally upregulated. By additionally inducing key differentiation markers of osteoblasts-amongst others, runt-related transcription factor 2 (RUNX2), osterix (OSX), osteopontin (OPN), and alkaline phosphatase-YAP is also involved in supporting the differentiation of PDLCs into osteoblasts (Figure 2) [141][142][143]. An orthodontic tooth movement (OTM) rat model as well as PDLCs in vitro experiments specifically proved that not only YAP but also TAZ supports osteogenic differentiation.…”
Section: Mechanotransduction To the Core: Yap/taz In The Periodontiummentioning
confidence: 98%